2021
DOI: 10.1016/j.rmed.2021.106491
|View full text |Cite
|
Sign up to set email alerts
|

Mepolizumab effectiveness in patients with severe eosinophilic asthma and co-presence of bronchiectasis: A real-world retrospective pilot study

Abstract: doi: medRxiv preprint NOTE: This preprint reports new research that has not been certified by peer review and should not be used to guide clinical practice.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 52 publications
2
23
0
2
Order By: Relevance
“…Another interesting result that emerges from our data is the confirmation, already seen in previous articles [ 8 , 24 , 25 , 26 , 27 ], that anti-Il-5 and anti-IGE biological therapy have been shown to be effective in reducing blood eosinophilia and in controlling severe asthma, regardless of whether patients also had bronchiectasis not due to CF or ABPA.…”
Section: Discussionsupporting
confidence: 86%
“…Another interesting result that emerges from our data is the confirmation, already seen in previous articles [ 8 , 24 , 25 , 26 , 27 ], that anti-Il-5 and anti-IGE biological therapy have been shown to be effective in reducing blood eosinophilia and in controlling severe asthma, regardless of whether patients also had bronchiectasis not due to CF or ABPA.…”
Section: Discussionsupporting
confidence: 86%
“…However, whilst the efficacy of mepolizumab is well documented, real-life data from independent sources on its effectiveness are currently limited, although growing through case series and global cohorts [ 13 , 14 ]. Also, several single-centre real-life studies have shown evidence of the effectiveness of mepolizumab [ 15 18 ]. Moreover, the stringent selection criteria adopted by clinical trials in general and by monoclonal antibody development programs in severe asthma are highly restrictive [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The precise effects of anti-IL5/IL5R antibodies on FeNO remain unknown since this outcome was not included in phase 3 studies. However, a prospective real-life study on Benralizumab (J-BEST), 19 a retrospective study on anti-IL5 therapies by Ramonell et al 20 and a real-world settings study on Mepolizumab 21 reported no significant change in FeNO despite a significant reduction in blood eosinophils 19 , 21 and significant clinical benefits from the therapy. 19–21 These suggest that the therapeutic effect of anti-IL5/IL5R does not correlate with FeNO levels.…”
Section: Discussionmentioning
confidence: 99%